The Differential Expression of Aqueous Soluble Proteins in Breast Normal and Cancerous Tissues in Relation to Stage and Grade of Patients. (9th December 2010) - Liang, Seng; Singh, Manjit; Gam, Lay-Harn
Abstract : Breast cancer is a leading cause of female deaths worldwide. In Malaysia, it is the most common form of female cancer while Infiltrating ductal carcinoma (IDC) is the most common form of breast cancer. A proteomic approach was used to identify changes in the protein profile of breast cancerous and normal tissues. The patients were divided into different cohorts according to tumour stage and grade. We identified twenty-four differentially expressed hydrophilic proteins. A few proteins were found significantly related to various stages and grades of IDC, amongst which were SEC13-like 1 (isoform b), calreticulin, 14-3-3 protein zeta, and 14-3-3 protein eta. In this study, we found that by defining the expression of the proteins according to stages and grades of IDC, a significant relationship between the expression of the proteins with the stage or grade of IDC can be established, which increases the usefulness of these proteins as biomarkers for IDC.